Analysis on Construction Technology and Quality Control of Asphalt Pavement in Highway Engineering - Wang, Yanfeng (Journal of Theory and Practice of Management Science, 2023)
With the development of the times and the progress of society, people's requirements for quality of life have become increasingly high. The number of private cars has increased, and road construction projects have also continued to increase. Asphalt pavement has been widely used in road engineering due to its advantages such as high durability, convenient material extraction, and road smoothness. However, the complexity of asphalt pavement construction has brought many difficulties to the construction unit. Strict control over the construction technology and quality of asphalt pavement can not only ensure the normal operation of construction, but also reduce costs. This article focuses on the construction technology and related quality control measures of highway asphalt pavement.